Expatriate partners : career identity, career capital and subjective well-being perspectives - Kanstrén, Kaisu (Vaasan yliopisto, 2021)
This dissertation aims to deepen the understanding of expatriate partners’ career identities, career capital development and subjective well-being (SWB). The dissertation consists of three individual articles, and draws on semi-structured interviews with a total of 30 Finnish partners of expatriates. Two different qualitative approaches were applied in the analysis (narrative analysis and thematic analysis). The findings of this research show that expatriation has a considerable impact on expatriate partners´ career identity reconstruction, and partners share several learning experiences that develop their career capital. International relocation also causes significant changes in the expatriate partners’ condition resources that lead to changes in SWB either directly or through affecting their energy and personal resources. Additionally, resource gain spirals seem to have a more powerful effect on partners’ SWB than resource loss cycles. The results also highlight the importance of partners’ career self-management skills, personal agency, and self-directed activity whilst abroad. The contribution of this dissertation is twofold. First, in terms of theoretical and methodological contributions the study brings new knowledge to the international HRM literature and partner research. Also, the narrative approach, Career Capital theory, and Conservation of Resources theory proved to offer a useful theoretical tool to study partners. Second, as a practical contribution the study offers insights for international HRM professionals who plan, execute and assess their organizations’ global mobility practices by identifying and highlighting the importance of partner issues.

Tämän väitöskirjan tavoitteena on tarkastella ekspatriaattipuolisoiden uraidentiteettejä, urapääoman kehittymistä ja subjektiivista hyvinvointia. Väitöskirja koostuu kolmesta artikkelista sekä niiden pohjalta laaditusta yhteenvedosta. Tutkimusaineisto kerättiin yhteensä 30 suomalaiselle ekspatriaattipuolisolle tehdyillä puolistrukturoiduilla haastatteluilla. Aineiston analyysissä käytettiin kahta laadullista analyysimenetelmää (narratiivinen analyysi ja temaattinen analyysi). Tutkimuksen tulokset osoittavat, että kansainvälisellä työliikkuvuudella on huomattava vaikutus ekspatriaattipuolisoiden uraidentiteettien uudelleenrakentumiselle. Heillä on myös useita urapääomaa kehittäviä oppimiskokemuksia. Lisäksi liikkuvuus saa aikaan merkittäviä muutoksia puolisoiden hyvinvointiin vaikuttavissa resursseissa. Resurssien saavuttamisella näyttää puolestaan olevan voimakkaampi vaikutus hyvinvoinnille kuin niiden menettämisellä. Tulokset myös korostavat puolisoiden oman uran johtamisen taitojen, aktiivisen toimijuuden ja itseohjautuvuuden merkitystä. Teoreettisesta näkökulmasta väitöskirja tarjoaa uutta tietoa kansainvälisen henkilöstöjohtamisen ja puolisotutkimuksen alueelle. Se myös osoittaa, että narratiivinen lähestymistapa, urapääomateoria ja Conservation of Resources -teoria tarjoavat hyvät viitekehykset puolisoiden tutkimiseen. Käytännön HR-toimijoille väitöskirja tarjoaa näkemyksiä puolisoiden ja heille tarjottavan tuen tärkeydestä.
Ekspatriaattipuolisot : uraidentiteetti-, urapääoma- ja hyvinvointinäkökulmat
Keywords: expatriate partners; career identity; development of career capital; subjective well-being; career; career development; working abroad; human resources; relocation; fi=Henkilöstöjohtaminen|en=Human Resource Management|